Lärarna och lämpligheten: studier av underkännandets praktik - Gerrevall, Per (Pedagogisk forskning i Sverige, 2018)
Education of teachers and teacher competence has been an important field since the establishment of Pedagogy as science. This article relates to research concerning teacher competence and conditions for admission to teacher education. The purpose is to identify what is characterized as ineligible in connection with admission to teacher education, in assessing becoming teachers’ pedagogical actions, and in professional teachers’ vocational practice. Within a research group at Linnaeus University, we have in two projects studied the gatekeeping function to the teaching profession. The core of the projects consists of the assessment of eligibility that takes place before and during teacher training as well as during teachers’ professional practice. On admission to teacher education, it is mainly on communicative and relational grounds that an applicant may be deemed ineligible to become a teacher. In teacher education a didactical dimension is added as well as an analytical and reflective dimension, which means being able to reflect critically over practice on a scientific ground, or on ethical grounds. In teachers’ professional practice, shortcomings in communicative and relational competence as well as actions that contradict ethical grounds constitute predominant reasons for being considered ineligible. Shortcomings in educational skills are generally handled at school level.